Tourism and changes in the cultural expressions of the Native Community Pampa Michi - Santos Shingari, Omar Daniel (2022)
Tourism is a social activity and as such generates impacts. In some cases it can be an ally for the preservation of culture, but in other cases it can cause important changes in the culture of the people, especially when it is carried out in an unplanned manner. This paper describes the changes in the cultural expressions of the Pampa Michi Native Community that were exposed to tourism between 1998 and 2019. The study is conducted from a qualitative approach and narrative design; for this purpose, semi-structured interviews and life histories were used as instruments for data collection. According to the results, the cultural expressions of the community have changed and now show new dances such as the pandilla or anaconda, as well as new designs and colors in their typical clothing, and new products and materials in their handicrafts. In conclusion, the cultural expressions of the community that were exposed to the tourist activity changed since the beginning of tourism in the locality in 1998, until 2019, the year of the beginning of the pandemic.